PERBANDINGAN SAJIAN MAKANAN DALAM UPACARA BESAR SUKU TENGGER: ANALISIS NILAI BUDAYA - Lestari, Dwi Indah (Acintya, 2023)
The Tengger tribe is one of the majority Hindus, the sect they profess is mostly Mahayana Hinduism, but not a few are also Muslims. The spread of the Tengger tribe community has expanded not only in the Lumajang argosari area, but also to the Malang area. The Tengger tribe is the tribe best known for the least criminal acts in Indonesia, not only that the Tengger tribe is famous for a tribe that has a very strong tolerance value both in religious life and in community life. This research uses research methods of literature studies or literature reviews, data taken from various references ranging from articles, websites, journals, theses and theses. From the various data that the author has collected, the author can provide conclusions about the differences in presentation in each traditional ceremony. Because the Tengger people beieve that with the dishes they give every time there is a major religious event they do, they always have special dishes as a thanksgiving, the Tengger tribe people believe that by giving symbolic food offerings to the spirits that have left, making them more docile and not disturbing living creatures. The dishes given do not have to be luxurious food but complete according to the provisions of each traditional event.  Keywords: tolerance, serving, custom